Arisan as a Form of Social Solidarity for Housewives in Klangenan Plot Block RT 02 RW 05, Klangenan District, Cirebon Regency - Uun Machsunah; Muhammad Iqbal Manshur; Dina Kholis Aziza; Hesti Nauly Fitri Agasya (Ann Publisher, 2024)
The purpose of this study was to determine the extent of solidarity of housewives in Klangenan Plot Block RT 02 RW 05, Klangenan District, Cirebon Regency through social gathering activities. What are the factors behind the gathering activities of the housewives so that they become a medium of solidarity for their members? This study used a qualitative descriptive approach. Data collection using observation, interviews, and documentation. The author uses field research (field research), collecting data at the research site. Research findings show that the factors that encourage social gathering activities as a medium of social solidarity are: Social gathering activities to strengthen friendship because it is difficult to meet on weekdays; Perform roles related to rights and obligations; Foster the nature of cooperation and social solidarity; Building trust among fellow arisan members; Building social networks; Forming and strengthening norms; Train its members to organize well; and Managing conflict becomes a constructive solution.